NURSE CALL OTOMATIS DENGAN SENSOR BEAT PER MINUTES (BPM) BERBASIS INTERNET OF THINGS (IOT) - Purwiyanto Purwiyanto; Cahya Vikasari; Dwi Novia Prasetyanti; Galih Mustiko Aji (Jurnal Poli-Teknologi, 2019)
ABSTRACTNurse call is a device which used by inpatient care facility to call nurse or other medical staff. Within some condition, the patient can’t make a call. Therefore, it is necessary to make a device that function for monitoring patient’s heartbeat as an indicator to give medical service. The sensor of Beat per Minutes is installed on the patien’s body that connected to network of Internet of Things (IoT) in order to be capable of communicating with the available information System in Nurse station. The sensor implementation on the network of IoT shows that the sensor data from 60 to 100 bpm is a normal condition. The more or less sensor data from the normal condition will give a warning on the Information System in Nurse Station.Keywords: Nurse call, Internet of Things, heart rate Sensor, Embedded System, Microcontroller.ABSTRAKNurse call merupakan perangkat yang digunakan pasien rawat inap untuk memanggil perawat atau petugas medis lainnya. Dalam beberapa kondisi pasien tidak dapat melakukan panggilan, oleh karena itu diperlukan suatu perangkat yang berfungsi untuk memantau detak jantung pasien sebagai indikator untuk memberikan pelayanan medis. Sensor Beat per Minutes (BPM) dipasang pada tubuh pasien yang terhubung pada jaringan Internet of Things (IoT) agar dapat berkomunikasi dengan Sistem Informasi yang ada di Nurse Station. Implementasi sensor pada jaringan IoT menunjukkan data sensor 60 sampai dengan 100 bpm merupakan kondisi normal. Data sensor lebih atau kurang dari kondisi normal akan memberikan peringatan pada Sistem Informasi yang terdapat di Nurse Station.Kata Kunci: Nurse call, Internet of Things, Sensor detak jantung, Sistem embedded, Mikrokontroler.